Pengembangan Motif Batik Sedap Malam Sukabumi menggunakan Perangkat Lunak Batik - Ganefiani, Shafanissa (Mahesa Research Center, 2025)
Batik is an Indonesian cultural heritage that continues to grow along with technological innovation. This research aims to develop the batik motif of Sedap Malam Sukabumi using jBatik software as an effort to modernize and increase competitiveness. The research method used is a three-stage design process, which includes problem definition and research, creative exploration, and implementation. The initial stage is carried out by exploring the existing Sedap Malam motif, followed by a digital design process using jBatik to produce a more dynamic motif variation. Research results show that the use of fractal technology in jBatik is able to increase the precision and efficiency of motif design. The implementation of this motif on batik stamp and its application in ready-to-wear fashion design proves that the Sedap Malam motif can be adapted in the modern fashion industry. With a technology-based approach, Sukabumi batik has the potential to be more known and competitive in the global market.